Low temperature complete combustion of dilute toluene and methyl ethyl ketone over Mn-doped ZrO2 (cubic) catalysts - Choudhary, Vasant R.; Deshmukh, G. M.; Pataskar, S. G. (Journal of Chemical Technology and Biotechnology, 2005)
Combustion of dilute toluene and methyl ethyl ketone over Mn-doped ZrO2 catalysts prepared using different precipitating agents, such as tetra-alkyl ammonium hydroxides and NH4OH, having Mn/Zr ratios from 0.05 to 0.67, and calcined at different temperatures has been thoroughly investigated. The Mn-doped ZrO2 catalyst shows high toluene or methyl ethyl ketone combustion activity, particularly when its ZrO2 is in cubic form, when its Mn/Zr ratio is close to 0.2, and when it is prepared using tetra-methyl ammonium hydroxide as a precipitating agent and calcined at 773 K. (c) 2005 Society of Chemical Industry.
Keywords: combustion of methyl ethyl ketone; combustion of toluene; Mn-doped ZrO2 catalyst

Low-temperature complete combustion of a dilute mixture of methane and propane over transition-metal-doped ZrO2 catalysts: effect of the presence of propane on methane combustion - Choudhary, Vasant R.; Deshmukh, G. M.; Pataskar, S. G. (Environmental Science and Technology, 2005)
Complete combustion of dilute methane alone or a dilute mixture of methane and propane over transition-metal (viz. Mn, Co, Cr, Fe, and Ni)-doped ZrO2 (cubic) catalysts at different temperatures (523-873 K) and a space velocity of 51 000 CM3 center dot g(-1)center dot h(-1) has been investigated for controlling methane and propane emissions from exhaust gases. The catalysts are compared for their catalytic ignition temperature and activity in the combustion of propane and methane in the presence of each other. The methane combustion activity of all the catalysts is strongly influenced by the presence of propane; it is decreased markedly. In the combustion of mixed methane and propane the Mn-doped ZrO2 and Cr-doped ZrO2 catalysts show the highest activity in the combustion of methane and propane, respectively; the Ni-doped ZrO2 shows the lowest activity in both cases. In the combustion of mixed methane and propane the propane combustion is enhanced but the methane combustion retarded when the Cr-doped ZrO2 and Mn-doped ZrO2 catalysts in a 1:1 ratio are used together in different ways (mixed or in layers).